THE IMPORTANCE OF CULTIVATED PLANTS IN HUMAN LIFE - Ahror Abdusalimov; Tolqin Normuratovich Absamatov (European Science Publishing, 2024)
This article provides information on the history of the beet (Beta) plant, its distribution area, its biology and varieties, cultivation technology, the nutritional value of its root, its importance in human life, and its negative aspects.
Keywords: Beet plant, root fruit,